Pfibrolizer: A new paradigm for large scale electrospinning from lessons learnt from Malaysian kitchen - Sunil, Vaishak; Ling, Jin Kiong; Yasin, Amina; Izan Izwan, Misnon; Rajan, Jose (2021)
Electrospinning is a fiber production method, in which a liquid droplet is electrified to generate a jet, followed by stretching and elongation to generate fibers. Electrospinning setup mainly consists of 3 parts, a spinneret, high voltage source and a collector. The currently available electrospinning spinneret in markets has several drawbacks which limits its efficiency. Inspired from the Malaysian kitchen, we have designed a simple electrospinning spinneret head which is beneficial for large scale nanofiber production. This design also allows the user to easily modify the spinneret according to the requirements of morphology and number of fibers.